Changes in myocardial iron content following administration of intravenous iron (Myocardial‐IRON): Study design. Issue 6 (5th June 2018) - Miñana, Gema; Cardells, Ingrid; Palau, Patricia; Llàcer, Pau; Fácila, Lorenzo; Almenar, Luis; López‐Lereu, Maria Pilar; Monmeneu, Jose V.; Amiguet, Martina; González, Jessika; Serrano, Alicia; Montagud, Vicente; et al.
Abstract : Treatment with intravenous ferric carboxymaltose (FCM) has been shown to improve symptoms, functional capacity, and quality of life in patients with heart failure and iron deficiency. However, the underlying mechanisms for these beneficial effects remain undetermined. The aim of this study is to quantify cardiac magnetic resonance changes in myocardial iron content after administration of intravenous FCM in patients with heart failure and iron deficiency and contrast them with parameters of heart failure severity. This is a multicenter, double‐blind, randomized study. Fifty patients with stable symptomatic heart failure, left ventricular ejection fraction <50%, and iron deficiency will be randomly assigned 1:1 to receive intravenous FCM or placebo. Intramyocardial iron will be evaluated by T2* and T1 mapping cardiac magnetic resonance sequences before and at 7 and 30 days after FCM. After 30 days, patients assigned to placebo will receive intravenous FCM in case of persistent iron deficiency. The main endpoint will be changes from baseline in myocardial iron content at 7 and 30 days. Secondary endpoints will include the correlation of these changes with left ventricular ejection fraction, functional capacity, quality of life, and cardiac biomarkers. The results of this study will add important knowledge about the effects of intravenous FCM on myocardial tissue and cardiac function. We hypothesize that short‐term (7 and 30 days) myocardial iron content changes after intravenous FCM, evaluated by cardiac magnetic resonance, will correlate with simultaneous changes in parameters of heart failure severity. The study is registered at http://www.clinicaltrials.gov (NCT03398681).